Acute diverticulitis masquerading as unilateral sciatica-like symptoms. Issue 6 (1st November 2020) - Novoselova, Victoria; Lacasse, Alexandre
ABSTRACT: A 66 year-old female presented with Systemic Inflammatory Response Syndrome (SIRS), severe left thigh pain, and localized edema. Non-contrast Computed Tomography (CT) suggested the presence of air in the left thigh and no evidence of an acute intra-abdominal process. Blood cultures grew an anaerobic gram-negative microorganism identified as Bacteroides fragilis . Repeat CT imaging with intravenous (IV) contrast revealed acute diverticulitis and the presence of a retroperitoneal abscess with extension to the thigh muscle. Along with antimicrobial therapy, surgical intervention was needed. The patient required a sigmoid resection with end-colostomy which led to clinical improvement.